2007
DOI: 10.1021/bi7011756
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Mini-B, a Functional Fragment of Surfactant Protein B, in Detergent Micelles,

Abstract: Surfactant protein B (SP-B) is essential for normal lung surfactant function, which is in itself essential to life. However, the molecular basis for SP-B's activity is not understood and a high-resolution structure for SP-B has not been determined. Mini-B is a 34-residue peptide with internal disulfide linkages that is composed of the N- and C-terminal helical regions of SP-B. It has been shown to retain similar activity to full-length SP-B in certain in vitro and in vivo studies. We have used solution NMR to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
64
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 59 publications
3
64
0
Order By: Relevance
“…Our working hypothesis is that the SP-Css ion-lock 1 in lipids improves its surfactant functions by stabilizing α -helix through a close-range salt-bridge between the Glu − -20 and Lys + -24 residues. As a further test of this proposition, more detailed 3D information on the structure and membrane topography of SP-C ion-locks will be obtained using 13 C-FTIR spectroscopy (Gordon et al, 2000; Waring et al, 2005), 2D-NMR spectrometry (Sarker et al, 2007) and/or all-atom MD simulation techniques (Walther et al, 2010; Almlen et al, 2010). Additionally, polarized FTIR spectra of SP-C mimics in surfactant lipids should indicate the fatty-acyl chain orientation with respect to the peptide helical axis, and likewise show if there are any protein-induced perturbations in lipid conformations (Clercx et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Our working hypothesis is that the SP-Css ion-lock 1 in lipids improves its surfactant functions by stabilizing α -helix through a close-range salt-bridge between the Glu − -20 and Lys + -24 residues. As a further test of this proposition, more detailed 3D information on the structure and membrane topography of SP-C ion-locks will be obtained using 13 C-FTIR spectroscopy (Gordon et al, 2000; Waring et al, 2005), 2D-NMR spectrometry (Sarker et al, 2007) and/or all-atom MD simulation techniques (Walther et al, 2010; Almlen et al, 2010). Additionally, polarized FTIR spectra of SP-C mimics in surfactant lipids should indicate the fatty-acyl chain orientation with respect to the peptide helical axis, and likewise show if there are any protein-induced perturbations in lipid conformations (Clercx et al, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…Mini-B has been shown to retain certain activity of the full-length SP-B. 54 Two tails of the SP-C peptide (PDB ID: 1SPF) has been palmitoylated, which is crucial for its surface activity. 55 The complete molecular structure of the hydrophilic surfactant protein SP-A is not yet available.…”
Section: Methodsmentioning
confidence: 99%
“…More recently, 2D-NMR spectroscopy has elucidated the 3-D structure of reduced MB in an HFIP solution, and that of oxidized MB in sodium dodecyl sulfate (SDS) detergent micelles [21]. Similar to that noted above for oxidized MB (1SSZ) in HFIP, 2D-NMR analysis showed that the N- and C-terminal regions of reduced MB in HFIP (PDB: 2JOU) fold as α-helices (Figures 3A and 3B).…”
Section: Mini-b (Mb) and Super Mini-b (S-mb) Synthetic Peptidesmentioning
confidence: 99%